Cigarette smoke inhibits efferocytosis via deregulation of sphingosine kinase signaling: reversal with exogenous S1P and the S1P analogue FTY720. Issue 1 (20th January 2016) - Tran, Hai B; Barnawi, Jameel; Ween, Miranda; Hamon, Rhys; Roscioli, Eugene; Hodge, Greg; Reynolds, Paul N; Pitson, Stuart M; Davies, Lorena T; Haberberger, Rainer; Hodge, Sandra
Abstract : SPHK1/2 regulation of efferocytosis in macrophages offers a novel therapeutic approach for COPD. Abstract: Alveolar macrophages from chronic obstructive pulmonary disease patients and cigarette smokers are deficient in their ability to phagocytose apoptotic bronchial epithelial cells (efferocytosis). We hypothesized that the defect is mediated via inhibition of sphingosine kinases and/or their subcellular mislocalization in response to cigarette smoke and can be normalized with exogenous sphingosine-1-phosphate or FTY720 (fingolimod), a modulator of sphingosine-1-phosphate signaling, which has been shown to be clinically useful in multiple sclerosis. Measurement of sphingosine kinase 1/2 activities by [ 32 P]-labeled sphingosine-1-phosphate revealed a 30% reduction of sphingosine kinase 1 ( P < 0.05) and a nonsignificant decrease of sphingosine kinase 2 in THP-1 macrophages after 1 h cigarette smoke extract exposure. By confocal analysis macrophage sphingosine kinase 1 protein was normally localized to the plasma membrane and cytoplasm and sphingosine kinase 2 to the nucleus and cytoplasm but absent at the cell surface. Cigarette smoke extract exposure (24 h) led to a retraction of sphingosine kinase 1 from the plasma membrane and sphingosine kinase 1/2 clumping in the Golgi domain. Selective inhibition of sphingosine kinase 2 with 25 µM ABC294640 led to 36% inhibition of efferocytosis ( P < 0.05); 10 µM sphingosine kinase inhibitor/5C (sphingosine kinase 1-selective inhibitor) induced a nonsignificant inhibition of efferocytosis, but its combination with ABC294640 led to 56% inhibition ( P < 0.01 vs. control and < 0.05 vs. single inhibitors). Cigarette smoke-inhibited efferocytosis was significantly ( P < 0.05) reversed to near-control levels in the presence of 10–100 nM exogenous sphingosine-1-phosphate or FTY720, and FTY720 reduced cigarette smoke-induced clumping of sphingosine kinase 1/2 in the Golgi domain. These data strongly support a role of sphingosine kinase 1/2 in efferocytosis and as novel therapeutic targets in chronic obstructive pulmonary disease.